2022
DOI: 10.2427/12831
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Infant Complementary Feeding Pattern and Some Related Factors in Health Care Centers in Khorramabad, 2017 Year

Abstract: Objective: Inappropriate starting of complementary feeding is an important factor leading to infant growth delay and malnutrition. This study was aimed to determine the complementary feeding pattern and some related factors in health care centers in Khorramabad.  Methods: This cross-sectional study, included 300 one year old infants who had referred to nine health care centers in Khorramabad by multistage sampling. In present study, we used a questionnaire included individual information about mothers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It includes observing human behavior in interaction with the environment. In this research, it is found that the implementation of exclusive breastfeeding activities involves the transfer of knowledge and support, such as time and funding, effectively managed by 6,[69][70][71] Several aspects of the attention provided by health cadres in the exclusive breastfeeding program include the distribution of physical guidelines, such as empowerment manuals for breastfeeding mothers in the exclusive breastfeeding program. These manuals contain information about the benefits of exclusive breastfeeding, the correct method of breastfeeding, and the support that can be provided by family and the surrounding community.…”
Section: Elements In the Modelmentioning
confidence: 99%
“…It includes observing human behavior in interaction with the environment. In this research, it is found that the implementation of exclusive breastfeeding activities involves the transfer of knowledge and support, such as time and funding, effectively managed by 6,[69][70][71] Several aspects of the attention provided by health cadres in the exclusive breastfeeding program include the distribution of physical guidelines, such as empowerment manuals for breastfeeding mothers in the exclusive breastfeeding program. These manuals contain information about the benefits of exclusive breastfeeding, the correct method of breastfeeding, and the support that can be provided by family and the surrounding community.…”
Section: Elements In the Modelmentioning
confidence: 99%